Service pressure regulation in water distribution networks. (May 2019) - Galuppini, Giacomo; Creaco, Enrico; Toffanin, Chiara; Magni, Lalo
Abstract: Real time pressure control is commonly adopted in water distribution network management to reduce leakage. A numerical description of the dynamic behaviour of the water distribution network (WDN) is introduced, allowing simulations of different case studies. A local, linear model is then identified from simulated experiments in order to synthesise different control algorithms working with control time step of 1 s. A state-of-the-art control algorithm operating with control time step of some minutes is used as benchmark. Results prove that all the new controllers reduce the control error, suggesting that cost and communication overheads introduced by control time step reduction are well motivated by sensible benefits in terms of pressure regulation. Highlights: Real time pressure control allows leakage reduction in water distribution networks. Modern networks include communication wiring, allowing short sampling time. Control algorithms working with a sampling time of 1 second are proposed. Simulations are performed in two different network layouts. All the new algorithms outperform the benchmark in term of regulation error.